BASIC ETYMOLOGY OF THE STOMATOLOGICAL LANGUAGE: AN ESSAY - Grein, Narciso José; Martins, Wilson Denis (Archives of Oral Research, 2005)
The semiologic and stomatologic language may present some difficulties both to students and health professionals. Such dificulties may be justified by the lack of knowledge of greek and latin, since the scientific terminology is chiefly composed by roots from these languages. With no intention to present an exhaustive work, a list of roots was performed, containing some terms used in the daily practice of Dentistry, and Stomatology in special.